2015
DOI: 10.5194/hess-19-1193-2015
|View full text |Cite
|
Sign up to set email alerts
|

Use of field and laboratory methods for estimating unsaturated hydraulic properties under different land uses

Abstract: International audienceAdequate water management is required to im- prove the efficiency and sustainability of agricultural sys- tems when water is scarce or over-abundant, especially in the case of land use changes. In order to quantify, to pre- dict and eventually to control water and solute transport into soil, soil hydraulic properties need to be determined pre- cisely. As their determination is often tedious, expensive and time-consuming, many alternative field and laboratory tech- niques are now available… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 39 publications
2
26
0
10
Order By: Relevance
“…The distribution model of soil water is related to the AGB, root biomass, and plant species distribution. High yield requires more water and the presence of deep roots that absorb deeper soil water; and the different plant species have different transpiration rates (Siltecho et al, ; Wang et al, ; Wang et al, ). Previous studies have suggested that the root system of the leguminous grasslands was deeper, which resulted in a higher consumption of soil water than the consumption of the gramineous grasslands (Huang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution model of soil water is related to the AGB, root biomass, and plant species distribution. High yield requires more water and the presence of deep roots that absorb deeper soil water; and the different plant species have different transpiration rates (Siltecho et al, ; Wang et al, ; Wang et al, ). Previous studies have suggested that the root system of the leguminous grasslands was deeper, which resulted in a higher consumption of soil water than the consumption of the gramineous grasslands (Huang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The restoration of natural grasslands and the establishment of artificial grasslands are common practices in the arid areas of the world. In these landscapes and during the process of restoration, the soil water content (SWC) is the key limiting factor for vegetation growth (Siltecho et al, ; Wang, Fan, Cao, & Liang, ; Wang, Li, Xiao, Berndtsson, & Pan, ). Soil water is not only the basis for plant survival in terrestrial ecosystem, but also the most active part within the watershed water cycle because it affects plant growth, ecological environment construction, and the rational distribution and efficient utilization of water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation infiltration is the most important process for soil water supply in the arid regions (Leung et al, 2015). The efficiency of the rainfall transform into soil water highly depends on the infiltration capacity, and this process is very important for soil water replenishment in water shortage regions (Wang et al, 2007;Siltecho et al, 2015;Wang et al, 2016). Thus, the research of soil infiltration capacity is a vital issue for vegetation maintenance and sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of exactness for individual VGM parameters does not seem to be an essential issue (Bezerra-Coelho et al, 2018). For instance, Siltecho et al (2015) demonstrated that individual values of the VGM parameters, especially the parameters n and K s , are highly dependent on the measurement technique. However, this individual dependency is not translated into noticeable differences in further simulations of state variables.…”
Section: Hypothetical Experimentsmentioning
confidence: 99%